Influence of vascular risk factors and neuropsychological profile on functional performances in CADASIL: results from the MIcrovascular LEukoencephalopathy Study (MILES). (19th July 2013) - Ciolli, L.; Pescini, F.; Salvadori, E.; Del Bene, A.; Pracucci, G.; Poggesi, A.; Nannucci, S.; Valenti, R.; Basile, A. M.; Squarzanti, F.; Bianchi, S.; Dotti, M. T.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited cerebral small vessel disease that may lead to disability and whose phenotype modulators are still unknown. Methods In the MIcrovascular LEukoencephalopathy Study (MILES), we assessed the influence of vascular risk factors and the effect of different cognitive domains (memory, psychomotor speed and executive functions) performances on functional abilities in CADASIL in comparison with age‐related leukoencephalopathy (ARL). Results We evaluated 51 CADASIL patients (mean age 50.3 ± 13.8 years, 47.1% males) and 68 ARL patients (70.6 ± 7.4 years, 58.8% males). Considering vascular risk factors, after adjustment for age, CADASIL patients had higher mean BMI values than ARL patients. Stroke history frequency was similar in the two groups. After adjustment for age, more CADASIL patients were disabled (impaired on ≥2 items of the Instrumental Activities of Daily Living scale) in comparison with ARL patients, and CADASIL patients had worse functional performances evaluated with the Disability Assessment for Dementia (DAD) scale. In CADASIL patients, hypertension was related to both DAD score and disability. The cognitive profile of CADASIL and ARL patients was similar, but on a stepwise linear regression analysis functional performances were mainly associated with the memory index (β = −0.418, P < 0.003) in CADASIL patients and the executive function index (β = −0.321, P = 0.028) in ARL. Conclusions This study suggests that hypertension may contribute to functional impairment in CADASIL and that memory impairment has a large influence on functional decline in contrast with that observed in a sample of subjects with ARL.